Ammonia Gas Adsorption in Fixed Bed and Fluidized Bed Using Bentonite Particles - Gabriela Muntianu; Ana-Maria Georgescu; Ana-Maria Rosu; Nicoleta Platon; Vasilica Alisa Arus; Cosmin Valeriu Jinescu; Ileana Denisa Nistor (Applied Sciences, 2025)
The present paper investigates the ammonia adsorption kinetic from air on sodium bentonite particles and on aluminum pillared bentonite particles in fixed bed and fluidized bed. The sodium bentonite is used as adsorbents and as raw material for chemically modified bentonite with aluminum polyhydroxocations. The aluminum pillared bentonite is prepared by a classical pillaring process to create high porosity and to increase the ammonia particle surface contact. Adsorbents used were characterized by the following analysis: granulometric distribution, acid–base character determination by Thermal Programmed Desorption (TPD), elemental microanalysis by Energy Dispersive X-Ray coupled with scanning electron microscopy (EDX-SEM), X-Ray diffractograms, adsorption–desorption isotherms by Brunauer–Emmett–Teller method and distribution of pore sizes and pore volume calculation by Barrett–Joyner–Halenda method. The variable parameters used in ammonia adsorption capacity on bentonite particle determination are particles size, gas velocity and total gas flow rate. The parameters kept constant during the ammonia adsorption process on bentonite particles are geometric ratio, adsorbent mass and initial ammonia gas concentration. The ammonia adsorption capacity on sodium bentonite particles and on aluminum pillared bentonite particles was measured until bed saturation as a function of the gas–particle contact technique. The best results are obtained with homogeneous fluidization with small gas bubbles for the aluminum pillared bentonite particles after 100 s bed saturation with ammonia adsorption capacity of 0.945 mmol NH3/g. To complete the study, ammonia desorption determination was carried out by a thermo-desorption process in order to recover the used particles. The adsorbent particles studied proved to be high-performance materials in order to use them in ammonia air depollution. Fluidized bed adsorption can be an efficient technique to accelerate mass transfer between ammonia from air and adsorbent particles.